Utilization of Rice Husk Waste for Paper Raw Materials as An Arabic Calligraphy Media - Ahmad Zarnuji; Hanif Amrulloh; Isnaini Nur Azizah (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2019)
Rice husk is an organic waste found in Indonesia as a raw material for paper products. The society has not yet realized that the material could also be a medium of Arabic calligraphy. This research-based community service action aims to introduce the benefits of rice husk as a raw material for making paper. To practice the production of paper from rice husk as the basis for making Arabic calligraphy art, so it is needed to make a business community of paper production from rice husk based on Arabic calligraphy. By using the Asset-Based Community Development method, the community mentoring process is carried out by helping the business community of rice husk paper based on Arabic calligraphy during the production to the marketing process. To control the quality of the art of Arabic calligraphy, the EL-KA Lampung calligraphy community was involved. The result shows that the Arabic calligraphy created by the assisted community has high artistic value with different textures from rice husk paper, then it was created a rice husk paper business community based on Arabic calligraphy.